Emperor Nicholas I Orenburg Women’s Institute in the Second Half of the 19th—Early 20th Century - Varavva, Margarita (Voprosy obrazovaniya / Educational Studies Moscow, 2020)
Reformation of female education in Russia in the mid‑19th century led, among other things, to further evolution of closed class-specific women’s institutes of the boarding school type that provided secondary, religious, and secular education of girls. Historical documents and archival sources are used in this article to describe the organization and content of learning in Emperor Nicholas I Orenburg Women’s Institute, the largest institution of secondary female education in the vast Orenburg Governorate at the end of the 19th century. Institute education had a considerable social value for girls from civil and military middle-class families in the cities and remote suburbs of Orenburg Governorate in that it allowed them not only to acquire general knowledge but also to develop teaching skills that they could use to make a living. Evidence is provided that, given the local settings, Emperor Nicholas I Orenburg Women’s Institute matched most of the criteria of the institute education model typical of pre-revolutionary Russia, which transformed in response to society’s demands concerning female education. Discontinuous interest, insufficient elaboration of the problem, and historical oblivion of valuable local history materials dictated the need to crane out a body of archival sources and reconstruct the process of creating a unique educational phenomenon, which Emperor Nicholas I Orenburg Women’s Institute came to be.